2019
DOI: 10.3390/jcm9010115
|View full text |Cite
|
Sign up to set email alerts
|

The Feasibility and Effectiveness of a New Practical Multidisciplinary Treatment for Low-Back Pain: A Randomized Controlled Trial

Abstract: Low-back pain is a major health problem exacerbated by the fact that most treatments are not suitable for self-management in everyday life. Particularly, interdisciplinary programs consist of intensive therapy lasting several weeks. Additionally, therapy components are rarely coordinated regarding reinforcing effects, which would improve complaints in persons with higher pain. This study assesses the effectiveness of a self-management program, firstly for persons suffering from higher pain and secondly compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 61 publications
0
24
0
Order By: Relevance
“…Study objectives were pursued in a subsample of a multicentre single-blind 3-armed randomised controlled trial (RCT, trial No. DRKS00004977, study design see [26,27] within the MiSpEx network (https://mispex.de/machbarkeit-multimodales-training/). The 24-week study comprised five measurements: baseline (M1), after 3 weeks (M2), after 6 weeks (M3), after 12 weeks (M4) and after 24 weeks (M5), whereby only results related to M4 and M5 were reported here.…”
Section: Design and Proceduresmentioning
confidence: 99%
See 3 more Smart Citations
“…Study objectives were pursued in a subsample of a multicentre single-blind 3-armed randomised controlled trial (RCT, trial No. DRKS00004977, study design see [26,27] within the MiSpEx network (https://mispex.de/machbarkeit-multimodales-training/). The 24-week study comprised five measurements: baseline (M1), after 3 weeks (M2), after 6 weeks (M3), after 12 weeks (M4) and after 24 weeks (M5), whereby only results related to M4 and M5 were reported here.…”
Section: Design and Proceduresmentioning
confidence: 99%
“…The exercise intervention included four different sensorimotor exercises, of which two directly trained the core stabilizing and core surrounding muscles, while the other two indirectly trained upper and/or lower extremities (detailed description see [27,29,30]). At the centre-based phase, the subjects were guided by sports-and physiotherapists, while the home training was audio-guided by a DVD.…”
Section: Interventionmentioning
confidence: 99%
See 2 more Smart Citations
“…Low back pain (LBP) is one of the most common musculoskeletal disorders in the world, and about 90% of patients have nonspecific LBP with no obvious cause [1]. Lifestyle factors, such as sedentary jobs and obesity, have further increased the incidence of back pain [2]. Keegan suggested that decreased lordosis in the lumbar spine is the chief contributing factor in LBP caused by extensive sitting [3].…”
Section: Introductionmentioning
confidence: 99%